PEMBELAJARAN STUDI KASUS KEWIRAUSAHAAN UNTUK PENGEMBANGAN EKONOMI WILAYAH (STUDI KASUS PERANCANGAN DAN SDM UMKM KONVEKSI ELEANOR) - Abdussalam, Abdussalam; Jiehad Akbar Pria Utamay, Jiehad Akbar Pria Utamay; Budiman Fauzi, Budiman Fauzi; Musyfiq Amrullah , Musyfiq Amrullah; Iwan Satriyo Nugroho, Iwan Satriyo Nugroho (Media Nusantara, 2021)
This research aims to provide an overview of project-based field learning and student-based learning. Learning is carried out at MSMEs operating in the textile sector. Collaboration between the Nahdlatul Ulama Islamic Economics College (STEI) and the Nusantara Islamic University (UNINUS). Field learning was carried out at UMKM Eleanor. This textile company is an Eleanor UKM which operates in the field of children's clothing, located in Ciparay, Bandung Regency. This small and medium enterprise (UKM) produces children's clothes made from t-shirt fabric which is used to meet the needs of the buying public and several customers. The types of t-shirt fabric produced include Cotton, Filament 75/D, Polyster 75/D, TC (tetoron Catton), Rayon, TR (Tetoron Rayon), CVC. The method uses a quantitative method by exploring Queuing Theory based on Industrial Engineering In production activities, at the end of the day, the graph of demand/orders from customers and other consumers for the above types of t-shirt fabric is felt to continue to increase. This is certainly an opportunity for the company to improve its fulfillment of requests/orders from customers and other consumers for the coming periods.